PENINGKATAN KETAHANAN PANGAN MELALUI INTERVENSI TEKNOLOGI PRODUKSI DAN KUALITAS PRODUK UNGGULAN GARAM DI DESA KARANGANYAR SUMENEP MADURA - Arendra, Anis; Akhmad , Sabarudin; Dzulkarnain, Iskandar; Asmoni, Asmoni (Jurnal Abdimas Bina Bangsa, 2025)
The competitiveness of salt produced by local farmers in Kalianget District, Sumenep Regency, East Java is still low. The production capacity of local salt is unstable, with inconsistent quality, which leads to the rejection of local salt as raw material in salt processing factories. This is further exacerbated by disputes over the grading of salt quality. Our activities aim to raise awareness, knowledge, and skills among salt farmer groups in ensuring the quality of local salt and increasing its production. Building awareness about quality assurance is a preliminary activity to prepare salt farmer groups for participating in improving the quality of local salt. This initial activity also involves the MBKM KKN (Community Service Program) in village development, entrepreneurship, and internships. Meanwhile, the design, fabrication, assembly, and installation of equipment for improving the quality of local salt and rapid test instruments for local salt quality are carried out off-site at the Manufacturing Systems Laboratory, Faculty of Engineering, Trunojoyo University, and on-site at the Salt Farmer Group location in Kalianget District. The implementation of this activity involves MBKM Product Development, Entrepreneurship, and Internship programs. The output of this activity is the development of equipment ready for implementation, including tools to improve brine quality and rapid test instruments for local salt quality. The empowerment of business partners for regional superior products among the salt farmer groups includes the provision of equipment grants accompanied by technology transfer assistance for operations, maintenance, and governance of local salt production. The increase in local salt productivity is achieved by preventing damage to the salt quality during the production process, ensuring that no more local salt is rejected as raw material in salt processing factories. This is also supported by the rapid test instrument for local salt quality to strengthen the bargaining position of salt farmers